“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé